Experimental study and simulation of the interface shear deformation behavior in AISI304/Q235 clad plate with thin cladding layer - Zhanzhou Liu; Yulin Shao; Haochen Ding; Chi Zhang; Zhendong Sheng; Huaibei Zheng; Liwen Zhang (Journal of Materials Research and Technology, 2023)
The mechanical properties and interface damage characteristics of hot-rolled bonded stainless steel/carbon steel (SS/CS) clad plate with thin cladding were investigated. The focus is on mechanical property-microstructure relationships in shear deformation. In detail, the mechanical response of the cladding components and clad plate were characterized. Then a hybrid numerical–experimental identification procedure for the cohesive zone model (CZM) in the simulation of heterogeneous SS/CS interface using finite element (FE) method was developed. A mixed-mode bilinear CZM, considering the anisotropy of the thin cladding was coupled FE model, showing a high accuracy for predicting the shear deformation behavior. The results showed obvious differences in the microstructure and mechanical properties of the SS and CS layers and the formation of an inhomogeneous interfacial layer. Additionally, the bond strength and delamination position of SS/CS clad plate are highly dependent on the interfacial oxide distribution and elemental diffusion behavior. Interestingly, the thin cladding is subjected to bending moments in shear deformation, resulting in delamination of the interface that is not completely dominated by one shear mode. And these abrupt interfacial failures could be clarified via stress-strain state and local damage analysis of the well-reproduced FE model of cladding material.